Social sustainability and local authorities: What is the relationship between spending commitments and social issues?. (September 2019) - Tafuro, Alessandra; De Matteis, Fabio; Preite, Daniela; Costa, Antonio; Mariella, Leonardo; Treviso, Giuliana
Highlights: We test if there is a relationship between the social expenses incurred by local authorities and their social issues. We analyse the social expenses of the Italian provincial capitals (n. 116) and some social indicators. We select the social indicators through interviews and statistical process. The relationship between the values is measured through Spearman's correlation coefficient. The local governments' financial commitment in social policies results "indifferent" to the real social needs.